2020
DOI: 10.1016/j.jaci.2019.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-specific IgE levels and the ability of IgE-allergen complexes to cross-link determine the extent of CD23-mediated T-cell activation

Abstract: Background: CD23 mediates IgE-facilitated allergen presentation and subsequent allergen-specific T-cell activation in allergic patients. Objective: We sought to investigate key factors regulating IgEfacilitated allergen presentation through CD23 and subsequent T-cell activation. Methods: To study T-cell activation by free allergens and different types of IgE-Bet v 1 complexes, we used a molecular model based on monoclonal human Bet v 1-specific IgE, monomeric and oligomeric Bet v 1 allergen, an MHC-matched CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(51 reference statements)
3
13
0
Order By: Relevance
“…These findings suggest that the number of IgE molecules bound per allergen may play an essential role in this complex formation and binding. This was confirmed recently in a study by Villazala-Merino et al 70 where non-FcεRI cross-linking monoclonal IgE-monomeric allergen complexes, i.e. (one IgE molecule binding two Bet v1 molecules) could enhance T cell activation.…”
Section: Role Of Ige In Enhancing T Cell Responsessupporting
confidence: 58%
“…These findings suggest that the number of IgE molecules bound per allergen may play an essential role in this complex formation and binding. This was confirmed recently in a study by Villazala-Merino et al 70 where non-FcεRI cross-linking monoclonal IgE-monomeric allergen complexes, i.e. (one IgE molecule binding two Bet v1 molecules) could enhance T cell activation.…”
Section: Role Of Ige In Enhancing T Cell Responsessupporting
confidence: 58%
“…However, the formation of allergen multimers would not only theoretically allow crosslinking of monoclonal antibodies [ 8 ], but was recently shown in detail in a study with Timothy grass pollen allergen [ 48 ]. Recent degranulation studies with an engineered Bet v 1 trimer confirm this notion [ 44 ]. Additional studies of our group with monoclonal antibodies against the major cow’s milk allergen BLG confirm these findings [ 49 ].…”
Section: Discussionmentioning
confidence: 87%
“…The findings of our internalisation studies were rather surprising: Bet v 1 internalisation appeared to be strictly antibody-dependent in the case of U937 monocytes, and unspecific and antibody-independent in the case of RPMI-8866 B cells. Based on the nature of these cell types and previous findings in B cells showing their IgE-dependent allergen internalisation and presentation to T cells, we would have assumed opposite results [ 44 , 45 , 46 ]. To our knowledge, only one study exists, which investigates Bet v 1 internalisation by monocytes and B cells [ 47 ].…”
Section: Discussionmentioning
confidence: 98%
“…Shamji validated the IgE-FAB assay and showed that serum IgE-FAB increased in a time-and dose-dependent fashion after grass pollen AIT 119,120 and correlated more closely with clinical response than accompanying elevated IgG4 levels This raised the possibility for IgE-FAB inhibition to predict individual responses to AIT 105 . Such blocking antibodies could also prevent captured allergen from stimulating IgE-producing cells thereby reducing boosts of IgE production caused by allergen exposure 70,121,122 .…”
Section: Induction and Function Of Allergen-specific Igg And Iga By Amentioning
confidence: 99%